At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
y = mx + b
add y to both sides:
3x + y - y + 2 = y
3x + 2 = y
y = 3x + 2
slope = 3x
m = 3 and (x, y) = (3, -4)
y + 4 = 3(x - 3)
y = 3x - 9 - 4
therefore, y = 3x - 13
add y to both sides:
3x + y - y + 2 = y
3x + 2 = y
y = 3x + 2
slope = 3x
m = 3 and (x, y) = (3, -4)
y + 4 = 3(x - 3)
y = 3x - 9 - 4
therefore, y = 3x - 13
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.